Problem Religiusitas dan Coping Spiritual pada Anak Berhadapan Hukum - Hasyim Hasanah; Ainun Fadlilah (Sawwa: Jurnal Studi Gender, 2018)
This study aims to describe the problem of religiosity and spiritual coping of children in the law (Anak Berhadapan Hukum/ABH) of the boarding school Raden Sahid Mangunnan Lor Demak. The type of research is field research with the psycho-socio-religious approach. The main data were obtained from interviews with children in the face of law and religious counselors. Techniques of data collections use interview and documentation. Methods of data analysis using Miles and Huberman models include data reduction, data presentation, data verification, and conclusion drawing. The result of the research shows that the ABH at boarding school Raden Sahid Mangunan Lor Demak has a problem of religiosity. The religious problem of ABH consists of beliefs, ritual practices, appreciation, low knowledge, and religious experience. The efforts to handle the problem of religiosity of ABH in Islamic boarding school Raden Sahid Mangunan Lor Demak, one of them with the efforts of spiritual coping through habituation and exemplary. Habituation is directed to the ritual of coaching and spiritual practice. Exemplary strived through the role of peers, religious counselors, and tutor Islamic boarding school in implanting spiritual values for the ABH. Spiritual and exemplary practice proven to reduces the religious problem of ABH especially on aspects of belief, knowledge, and appreciation.